2011
DOI: 10.1105/tpc.110.082768
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsis thalianaCheckpoint Kinase WEE1 Protects against Premature Vascular Differentiation during Replication Stress

Abstract: A sessile lifestyle forces plants to respond promptly to factors that affect their genomic integrity. Therefore, plants have developed checkpoint mechanisms to arrest cell cycle progression upon the occurrence of DNA stress, allowing the DNA to be repaired before onset of division. Previously, the WEE1 kinase had been demonstrated to be essential for delaying progression through the cell cycle in the presence of replication-inhibitory drugs, such as hydroxyurea. To understand the severe growth arrest of WEE1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 60 publications
6
83
0
Order By: Relevance
“…For this analysis, wee1 was used as a positive control and, consistent with previous data, was found to be highly sensitive to HU, whereas it shows no growth abnormalities on control medium (De Schutter et al , 2007; Cools et al , 2011). In contrast, root growth on HU of all tested cycb1 mutants was comparable to the growth of wild‐type plants (Fig 1C and D).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…For this analysis, wee1 was used as a positive control and, consistent with previous data, was found to be highly sensitive to HU, whereas it shows no growth abnormalities on control medium (De Schutter et al , 2007; Cools et al , 2011). In contrast, root growth on HU of all tested cycb1 mutants was comparable to the growth of wild‐type plants (Fig 1C and D).…”
Section: Resultssupporting
confidence: 68%
“…As a positive control, we used mutants in ku70 that were shown to grow as the wild type on medium without drugs (Cools et al , 2011). Whereas ku70 mutants were sensitive to BLM and grew only very little consistent with previous reports (Tamura et al , 2002; West et al , 2002; Cools et al , 2011), no significant difference was found between cycb1 single and double mutants versus the wild type again with the exception of cycb1;1 cycb1;2 (Fig 1E and F). Comparing root growth ratios on plates with and without BLM indicated that cycb1;1 cycb1;2 is also not hypersensitive to this drug (Fig EV3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDKB1;2, CDKB2;1, and KNOLLE [Yoshiyama et al, 2009;Missirian et al, 2014]), while directly up-regulating other factors (e.g. CYCB1;1, SMR-5,7 [Weimer et al, 2016a;Yi et al, 2014], and WEE1 indirectly [De Schutter et al, 2007, Cools et al, 2011). IR-induced SOG1 also transcriptionally activates DNA repair genes, including BRCA1 and RAD51 (Yoshiyama et al, 2009), which function in homologous recombination (HR)-based repair in S and G2 phase during normal growth (Shrivastav et al, 2008;Menges et al, 2003).…”
mentioning
confidence: 99%
“…HR repair can help to restore a damaged cell's genomic integrity in addition to the faster (Mao et al, 2008), predominating canonical nonhomologous end-joining repair pathway (Čermák et al, 2017). SOG1's induction of HR repair, in combination with cell cycle arrest, can prevent cell death from mitosis occurring prematurely in the presence of unrepaired DSBs (Furukawa et al, 2010;Cools et al, 2011;Léguillier et al, 2012;Yi et al, 2014).…”
mentioning
confidence: 99%